Cross-reactivity and inhibition myotoxic effects induced by Bothrops snake venoms using specific polyclonal anti-BnSP7 antibodies. (November 2017) - Melo, Lamartine L.; Mendes, Mirian M.; Alves, Lívia M.; Isabel, Thais F.; Vieira, Sâmela A.P.B.; Gimenes, Sarah N.C.; Soares, Andreimar M.; Rodrigues, Veridiana M.; Izidoro, Luiz F.M.
Abstract: Polyclonal antibodies raised in Balb-c mice against BnSP-7, a Lys-49 phospholipase A2, were used to measure cross reactivity against other snake venoms. Using ELISA, these antibodies were able to recognize PLA2 s isoforms present in venoms of botropic snakes at 1:6400, 1:3200 and 1:100 ratios (w/w). These antibodies highly recognized proteins of low molecular weight (∼14, 000) from crude snake venom Bp and Bm by Western Blotting. PLA2 these venoms, by alignment of primary structures demonstrated high identity with BnSP-7 PLA2, especially in the C-terminal region. However, the crude snake venom Bd and Bj, showed low recognition. The PLA2 activity of Bothrops pauloensis, Bothrops moojeni venoms or BpPLA2 -TXI was inhibited significantly when anti-BnSP-7 antibodies were incubated at 1:10 and 1:20 ratios (venoms or toxin:anti-BnSP-7, w/w), respectively. The myotoxic effect induced by the same venoms was also reduced significantly at 1:1, 1:10 and 1:20 ratios, by decreased creatine kinase levels. The anti -PLA2 polyclonal antibodies effectively recognized PLA2s from Bothrops pauloensis and Bothrops moojeni venoms, and neutralized specific catalytic and myotoxic activity.